2016
DOI: 10.5130/ajceb.v16i3.5158
|View full text |Cite
|
Sign up to set email alerts
|

Vectors of technical innovation delivery by small and medium Australian construction firms

Abstract: Long-established Schumpeterian theory on innovation assumes that significant innovations are generated by large companies with ample spare resources. The allocation of time and money to speculative endeavours with unclear outcomes has often been regarded as beyond the scope of small and medium-sized enterprises (SMEs). As a result, authorities sometimes advise SMEs to concentrate on the adoption of existing innovative products and processes rather than the generation of new creative ideas. Despite this traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…The implementation of technological innovation by small firms not necessarily needed any on-going relationships with universities or research bodies (Hardie, Manley 2008). Furthermore, it was evident that the reports identifying the effect of network capability were subject to the biased preference towards qualitative-based analysis of innovative offerings Hardie, Manley 2008;Hardie et al 2013). Hence, the present study conjectured that inter-organizational networks permit SMCFs to draw on resources beyond the firms' boundaries to innovate across a wider range of activities.…”
Section: Inter-organizational Networkmentioning
confidence: 92%
See 4 more Smart Citations
“…The implementation of technological innovation by small firms not necessarily needed any on-going relationships with universities or research bodies (Hardie, Manley 2008). Furthermore, it was evident that the reports identifying the effect of network capability were subject to the biased preference towards qualitative-based analysis of innovative offerings Hardie, Manley 2008;Hardie et al 2013). Hence, the present study conjectured that inter-organizational networks permit SMCFs to draw on resources beyond the firms' boundaries to innovate across a wider range of activities.…”
Section: Inter-organizational Networkmentioning
confidence: 92%
“…The understanding on these types of innovations remained unclear. One notable exception was the work by Hardie and Manley (2008) who observed that both the technological and organizational innovations could be hardly isolated from each other and small construction business needed to undertake the two types of innovations concurrently and synergistically to succeed. Such finding was meritorious in revealing the potential complementary effect of both technological and organizational types of new deliveries.…”
Section: Organizational Innovationsmentioning
confidence: 99%
See 3 more Smart Citations